Analyzing tagging patterns by integrating visual analytics with the inferential test - Choi, Yunseon (Institute of Electrical and Electronics Engineers Inc., 2015)
Due to the large volume and complexity of data, exploring data using visual analytics has become more helpful to interpret and analyze it. The box plot is one of graphical ways and is the most common technique for presenting and summarizing statistics. In this paper, we focus on discussing the tagging patterns by integrating visualization assessment using the box plot with the Shapiro-Wilk test. © 2015 Author.
Keywords: Data analytics; Data visualization; Digital libraries; Large volumes; Shapiro-Wilk tests; Social tagging; Visual analytics; Visualization; data analytics; data visualization; dept.ils; social tagging